Design of SMEBi: A Survey Application for Monitoring and Evaluation of Independent Midwifery Practice Based on Regulations - Ratni N; Fahrurizal Muldiana; Nissa Fatmawati; Tira Vita; Fitri Nurlina (Institut Kesehatan YARSI Mataram, 2025)
Monitoring and evaluation are essential in independent midwifery practice to ensure that services provided comply with established standards. Without proper monitoring, there may be a decline in service quality, increased medical errors, poor decision-making, and reduced public trust. However, there is a noticeable gap in the availability of integrated digital tools tailored for midwifery that combine regulatory compliance, performance tracking, and professional education. This study aims to design a native Android-based digital survey application named SMEBi (Survey Monitoring and Evaluation of Independent Midwife Practice Services) to address this gap. The development employed the Software Development Life Cycle (SDLC) method, focusing on the Requirements & Analysis and Design phases. Application development was carried out using Android Studio with Java programming, and SQLite was used as the local database to ensure offline access. The minimum device specification for running the app includes Android 10 OS, 4 GB RAM, and 2 GB of internal storage. The analysis revealed several critical system requirements: real-time data availability, standardized data formats, interactive reporting features, and embedded training and education modules. SMEBi offers user-friendly interfaces with key features such as login, dashboard, monitoring instruments, evaluation tools, and access to relevant legal references. This tool is expected to help midwives continuously assess and improve service quality while ensuring compliance with current regulations. ABSTRAK Monitoring dan evaluasi sangat penting dalam praktik kebidanan mandiri untuk memastikan bahwa layanan yang diberikan sesuai dengan standar yang telah ditetapkan. Tanpa monitoring yang tepat, dapat terjadi penurunan kualitas layanan, peningkatan kesalahan medis, pengambilan keputusan yang buruk, serta menurunnya kepercayaan masyarakat. Namun, masih terdapat kesenjangan dalam ketersediaan alat digital terintegrasi yang secara khusus ditujukan untuk praktik kebidanan yang mencakup kepatuhan regulasi, pelacakan kinerja, dan edukasi profesional. Penelitian ini bertujuan untuk merancang aplikasi survei digital berbasis Android native bernama SMEBi (Survey Monitoring and Evaluation of Independent Midwife Practice Services) untuk menjawab kesenjangan tersebut. Pengembangan aplikasi menggunakan metode Software Development Life Cycle (SDLC) dengan fokus pada tahapan Requirements & Analysis serta Design. Aplikasi dikembangkan menggunakan Android Studio dengan bahasa pemrograman Java, serta basis data lokal SQLite untuk mendukung akses offline. Aplikasi ini dirancang agar dapat berjalan pada perangkat dengan spesifikasi minimum OS Android 10, RAM 4 GB, dan penyimpanan internal 2 GB. Analisis kebutuhan menunjukkan adanya beberapa kebutuhan kritis, seperti ketersediaan data secara real-time, format data yang terstandarisasi, fitur pelaporan interaktif, serta modul pelatihan dan edukasi. Aplikasi SMEBi menyediakan antarmuka yang ramah pengguna dengan fitur utama seperti login, dashboard, instrumen monitoring, alat evaluasi, dan akses terhadap referensi hukum yang relevan. Alat ini diharapkan dapat membantu bidan dalam menilai dan meningkatkan kualitas layanan secara berkelanjutan sekaligus memastikan kepatuhan terhadap regulasi yang berlaku.